An 11‐year experience of acquired von Willebrand syndrome in children diagnosed with Wilms tumour in a tertiary referral centre. Issue 3 (12th September 2016) - Fosbury, Emma; Szychot, Elwira; Slater, Olga; Mathias, Mary; Sibson, Keith
Abstract: Wilms tumour (WT) is the commonest primary malignant renal tumour of childhood. Acquired von Willebrand syndrome (avWS) is a well‐described paraneoplastic phenomenon, but it is uncommon and may not be detected until clinically significant bleeding is encountered during interventional procedures. Previous studies on small cohorts of patients have determined an incidence of between 4 and 8%. We have performed a retrospective study on cases of WT presenting over an 11.5‐year period to a paediatric haematology/oncology unit in a tertiary referral centre to review the incidence of avWS, bleeding phenotype, management, and response to treatment of the primary pathology.